Jawabanmu

2014-04-25T00:15:37+07:00
Berbentuk jajar genjang_

jika ditranslasikan (-3, -5)
(x , y) ditranslasikan (a,b) ⇒ (x+a, y +b)

jadi bayangan A (-2, -7)
                      B (1, -7)
                     C (-1, -9)
                      D ( 2, 1)
2014-04-25T05:22:38+07:00
Kalo menurut saya sih.
 ABCD = Jajar genjang
translasi (-3.-5) = A(1.-2) + (-3.-5) = A1(-2.-7)
                                B(4.-2) + (-3.-5) = B1 (1.-7)
                                 C(2.-4) + (-3.5) = C1(-1-9)
                                D (5.-4) + (-3.-5) = D1 (2.-9)